Angiographic CT with intravenous contrast agent application for monitoring of intracranial flow diverting stents - Saake, Marc; Struffert, Tobias; Gölitz, Philipp; Ott, Sabine; Seifert, Frank; Ganslandt, Oliver; Dörfler, Arnd (Neuroradiology, 2012)
Introduction: Intracranial flow diverting devices are increasingly used to treat cerebral aneurysms. A reliable, noninvasive follow-up modality would be desirable. Our aim was to compare intra-arterial digital subtraction angiography (ia DSA) to angiographic computed tomography with intravenous contrast agent application (iv ACT) in the visualisation of flow diverting devices and aneurysm lumina. Methods: Follow-up monitoring by iv ACT (n=36) and ia DSA (n=25) in 14 patients treated with flow diverting devices for intracranial aneurysms was evaluated retrospectively. Images were evaluated by two neuroradiologists in anonymous consensus reading regarding the device deployment, wall apposition, neck coverage of the aneurysm, opacification of the vessel and device lumen, as well as the degree of aneurysm occlusion. Results: Corresponding ia DSA and iv ACT images were scored identically in all patients regarding the stent deployment, wall apposition and neck coverage, as well as the degree of aneurysm occlusion and patency status of the device and parent artery. Opacification of the parent vessel lumen and perfused parts of the aneurysm was considered slightly inferior for iv ACT in comparison with ia DSA (seven of 36 cases), without impact on diagnosis. Conclusions: We demonstrated the feasibility and diagnostic value of iv ACT in follow-up imaging of intracranial flow diverting devices. Due to its high spatial resolution and non-invasive character, this novel technique might become a valuable imaging modality in these patients. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Computed tomography; Flat detector; Flow diverting stent; Follow-up; Intravenous